Pengaruh Pembiayaan Jual Beli dan Nonperforming Financing terhadap Profitabilitas Bank Syariah (Studi Kasus Bank Syariah) - Ilik Bunadi; Septia Putri Amalia (Cakrawala Repositori IMWI, 2021)
This study examines how trade financing as well as non performing financing (NPF) affect the profitability of Islamic banking in Indonesia. The profitability is measured by return on assets. The sample selection method is purposive sampling and obtained seven Islamic banks are being sampled, that is Bank Muamalat Indonesia, Bank Syariah Mandiri, Bank BNI Syariah, Bank Bukopin Syariah, Bank Panin Syariah, Bank BCA Syariah, and BRI Syariah in 5 periods of observation. Multiple regression is used to analyze the data. The result shows that trade financing have no affect while non performing financing has negatively affect on the profitability of Islamic banks.